2014
DOI: 10.1155/2014/486078
|View full text |Cite
|
Sign up to set email alerts
|

Large Mucocele of the Appendix at Laparoscopy Presenting as an Adnexal Mass in a Postmenopausal Woman: A Case Report

Abstract: A 79-year-old female was referred to our Gynecologic Department presenting with a pelvic magnetic resonance imaging (MRI), showing an adnexal mass, later confirmed at the pelvic examination. The patient's routine laboratory tests were normal. A sonographic examination was performed with inconclusive results. Although the ultrasonography excluded the presence of vascularization and malignant degeneration, the adnexal localization appeared to be dubious. The laparoscopy and the subsequent histologic examination … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…Our patient's tumor markers were normal, and pelvic US and MRI both suggested an ovarian tumor that subsequently turned out to be appendiceal in orgin. Such situation is rare, although others reported similar possible uncertainty [ 6 , 9 ]. It is important to enhance the preoperative diagnosis of AM in order to increase the probability of anticipating it, and hence appropriate management, prevention of rupture at surgery, which may lead to pseudomyxoma peritonei; and also to prompt the intra-operative search for the presence of any synchronous colorectal neoplasm/s [ 4 ].…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Our patient's tumor markers were normal, and pelvic US and MRI both suggested an ovarian tumor that subsequently turned out to be appendiceal in orgin. Such situation is rare, although others reported similar possible uncertainty [ 6 , 9 ]. It is important to enhance the preoperative diagnosis of AM in order to increase the probability of anticipating it, and hence appropriate management, prevention of rupture at surgery, which may lead to pseudomyxoma peritonei; and also to prompt the intra-operative search for the presence of any synchronous colorectal neoplasm/s [ 4 ].…”
Section: Discussionmentioning
confidence: 98%
“…Hence, AM should be considered in the differential diagnosis of women presenting with adnexal mass on ultrasound in order to choose the best surgical approach [ 6 ]. The gynaecologist might benefit from more accurate investigational methods (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, mucinous cystadenoma was identified in 61.4% of the patients. [4,29] Mucinous cystadenoma is at the benign end of the spectrum with no risk of recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…[3] Mucocele of the appendix can be categorized in four histological types, including retention cyst, mucosal hyperplasia, mucinous cystadenoma, and mucinous cystadenocarcinoma. [4,5] The affected patients are usually above the age of 50 years. [6] Clinical signs include ab- USG showed a dilated tubular structure in the right iliac fossa, and CT revealed a long tubular structure distended with hypodense material with or without calcification in the wall of the appendix, together with mass effect in six cases.…”
Section: Introductionmentioning
confidence: 99%